Numerical analysis and transient thermal modeling of microwave dehydration of tomato: validation with experimental results - Arpaci, Emre; Atayilmaz, S. Ozgur; Gemici, Zafer; Demir, Hakan (SPRINGER, 2026)
In this study, a model of microwave dehydration of tomato slices was created. The model illustrates the temperature variations during the microwave dehydration of tomatoes by accounting for the moisture transport effect, while also demonstrating the electric field distribution and volume loss density. Model validation was carried out by experimental tests, and the absolute mean error was found to be 3.55 and 5.73 degrees C for 210 and 350W power levels, respectively. To reach more precise solutions, the thermophysical and dielectric properties of tomatoes were assumed to be temperature dependent. To explore drying kinetics and moisture transport in microwave drying, experimental results of tomato slices (5 mm thick) dried at 210 and 350W power are compared with four models, including three thin-layer drying models (Henderson-Pabis, Page, and Wang & Singh) and Fick's diffusion model. The Page and Wang Sing model was found to be in outstanding consensus with the empirical data in microwave drying process. The reasons for the poorer fit of the Fick model compared to the other models were explained. In addition, the difficulties of microwave dehydration CFD modeling and future recommendations were explained in detail. The findings and frameworks presented herein offer substantial knowledge that may broaden the investigative horizons of researchers within this subject.
Keywords: Microwave dehydration CFD modeling; Drying kinetics; HEAT; Thermodynamics; Chemistry